Tortilla Chezzy Wrap: Rosaresa / Rusnita Asmida Rusli and Nur Aressa Farhana Mohammad Azhar - Rusli, Rusnita Asmida; Mohammad Azhar, Nur Aressa Farhana (2022)
Tortilla Chezzy Wrap goal is to encourage people to taste the variety of premium and unique local products that will fulfil their cravings. Our vision is to inspire people to enjoy life more by encouraging them to always maintain their ideal weight and practices the healthy lifestyle food. Tortilla Chezzy Wrap is our main product. Customer can choose whether they want chicken or meat for their filling in the wrap. Other than, we also provided fresh ingredients such as cucumber, tomato and holland onion. For the sauce, customer also can choose whether they want chilli sauce, black paper, Thai sauce and cheese. If customer want to add cheese, we charge for RM1.50 because we use the premium cheese for our product. Based on the originality of the Tortilla Wrap flavours, we cook our own our filling such as we cook the meat and chicken with the high-quality butter with some garlic to raise the smell of our filling of chicken and meat. The originality of the flavour which was exclusive to our business. The purpose of our business is to promote our local customers that want to diet or to practices healthy lifestyle food. Since we are using a healthy ingredient, the product is primarily marketed to all age categories. Our target customer is not just local people, but tourists or foreigner are also one of our target markets as they are welcome to taste premium, healthy and freshy taste combination of our local business, Tortilla Chezzy Wrap with chicken and meat flavours. Tortilla Chezzy Wrap marketing strategy emphasize the quality and price of our product and services. We offer the affordable price because we want to give the best quality of our product towards our customer. They can enjoy our product without having any doubt. Customer can get the Tortilla Cheezy Wrap with the price RM5 for Tortilla Wrap Chicken and RM 6 for Tortilla Wrap Meat. We are do a partnership in our business. Rusnita Asmida and Nur Aressa is the partnership in this business. We don’t have a worker because every delivery is made by us. Rusnita Asmida is focusing on production and marketing while Nur Aressa is focusing on finance and operations.